2014
DOI: 10.11648/j.ijnfs.20140305.27
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nutritional Status and Prognosis in Surgical Intensive Care Unit: The Prognostic and Inflammatory Nutritional Index (PINI)

Abstract: Background Malnutrition is an independent factor of morbidity and mortality in patients at intensive care unit.The prognostic inflammatory and nutritional index (PINI) is frequently used as a marker of malnutrition but this scoring system was not studied in surgical intensive care units. The purposes of this study were to assist nutritional status with biomarkers and to search for a correlation between biological markers and prognosis, using the PINI. Methods A prospective, observational study was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Finally, the ICU patients have a moderate-to-severe degree of malnutrition and it has been shown that this degree of malnutrition has a significant negative impact on clinical outcome, factor that we have not taken into account when conducting this study. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the ICU patients have a moderate-to-severe degree of malnutrition and it has been shown that this degree of malnutrition has a significant negative impact on clinical outcome, factor that we have not taken into account when conducting this study. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Gharsallah et al found that an increased PINI score was not associated with all-cause mortality. However, they identified an initial increase followed by a progressive decrease in CRP and orosomucoid values and an increase in serum prealbumin and albumin values [10].…”
Section: The Pini Score In Intensive Care Unit (Icu)mentioning
confidence: 99%
“…This index represents a simple clinical assessment tool that combines two blood markers of inflammation, C-reactive protein (CRP) and α1-acid glycoprotein (also called orosomucoid), with two biomarkers that reflect the nutritional status, namely albumin and prealbumin (or transthyretin) [10][11][12]. The resulting value for PINI is a number value, with 1 representing the established reference value.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations